Associations between cardiometabolic disease severity, social determinants of health (SDoH), and poor COVID‐19 outcomes. Issue 7 (25th May 2022) - Howell, Carrie R.; Zhang, Li; Yi, Nengjun; Mehta, Tapan; Cherrington, Andrea L.; Garvey, W. Timothy
Abstract: Objective: This study aimed to determine the ability of retrospective cardiometabolic disease staging (CMDS) and social determinants of health (SDoH) to predict COVID‐19 outcomes. Methods: Individual and neighborhood SDoH and CMDS clinical parameters (BMI, glucose, blood pressure, high‐density lipoprotein, triglycerides), collected up to 3 years prior to a positive COVID‐19 test, were extracted from the electronic medical record. Bayesian logistic regression was used to model CMDS and SDoH to predict subsequent hospitalization, intensive care unit (ICU) admission, and mortality, and whether adding SDoH to the CMDS model improved prediction was investigated. Models were cross validated, and areas under the curve (AUC) were compared. Results: A total of 2, 873 patients were identified (mean age: 58 years [SD 13.2], 59% were female, 45% were Black). CMDS, insurance status, male sex, and higher glucose values were associated with increased odds of all outcomes; area‐level social vulnerability was associated with increased odds of hospitalization (odds ratio: 1.84, 95% CI: 1.38‐2.45) and ICU admission (odds ratio 1.98, 95% CI: 1.45‐2.85). The AUCs improved when SDoH were added to CMDS ( p  < 0.001): hospitalization (AUC 0.78 vs. 0.82), ICU admission (AUC 0.77 vs. 0.81), and mortality (AUC 0.77 vs. 0.83). Conclusions: Retrospective clinical markers of cardiometabolic disease and SDoH were independently predictive of COVID‐19 outcomes in the population.